2019
DOI: 10.3390/nu11010135
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Diet Quality as Measured by Malaysian Healthy Eating Index among Aboriginal Women (Mah Meri) in Malaysia

Abstract: Socioeconomic status and nutrition knowledge are the determining factors of food choices. However, their relationship with diet quality is ambiguous among aboriginal women in Malaysia. Henceforth, the objective of this study was to examine diet quality and its predictors among the aboriginal women from the Mah Meri ethnic group in Malaysia. Data on socioeconomic characteristics, nutrition knowledge, and 24-h dietary recalls were obtained through face-to-face interviews with the respondents. Household food inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 27 publications
3
38
1
1
Order By: Relevance
“…Modern society is confronting increased health issues as the population's eating habits and the lack of healthy food consciousness had caused obesity and poor nutrition and eating conditions among young adults [1]. About 2.8 million people die worldwide because due to being overweight or having melancholic obesity each year [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Modern society is confronting increased health issues as the population's eating habits and the lack of healthy food consciousness had caused obesity and poor nutrition and eating conditions among young adults [1]. About 2.8 million people die worldwide because due to being overweight or having melancholic obesity each year [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, Malaysians are facing issues of obesity and eating disorders [3]. Diet-related diseases are on the rise in Malaysia, and this is increasing the socioeconomic burdens on middle-income households [1]. Scientific evidence shows that unhealthy and unbalanced food increases the risk of hypertension, cardiovascular diseases, and diabetes [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high risk of double-burden malnutrition among other tribes Che Wong and Temuan was due to close the distance of their resettlements to town, which has increased their access to processed food. Furthermore, Chong et al [37] reported that food security was another leading factor for the occurrence of overweight and obesity among Mah Meri OA at Carey Island and Tanjung Sepat, Malaysia. Moreover, Nurul Hidayah et al [38] reported that dietary acculturation was significantly linked with increased body mass index (BMI) among OA adults in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%